2018
DOI: 10.1371/journal.pone.0206115
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to the implementation of clinical pharmacy services in a metropolis in Northeast Brazil

Abstract: BackgroundCLinical pharmacy services (CPS) are professional services provided by pharmacists, who use their skills and knowledge to take an active role in patient health. These services have expanded in health systems around the world. However, it is important to have a comprehensive understanding of factors that may hinder the implementation of CPS in health systems.ObjectiveTo identify pharmacists’ and managers’ perceptions of barriers regarding the implementation of CPS in some public health units in a metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 60 publications
1
20
0
5
Order By: Relevance
“…[7][8][9][10][11] Despite the evidence, however, the implementation, funding, and staffing of clinical pharmacy services continues to face numerous challenges. [12][13][14] As such, clinical pharmacy services can be particularly sensitive to changes that affect the allocation of resources within the health care facility.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Despite the evidence, however, the implementation, funding, and staffing of clinical pharmacy services continues to face numerous challenges. [12][13][14] As such, clinical pharmacy services can be particularly sensitive to changes that affect the allocation of resources within the health care facility.…”
mentioning
confidence: 99%
“…The literature based on qualitative studies that identify factors that may in uence the implementation of CPS is extensive [14,15,25,27,34] which begs the question, why carry out more studies on this topic? We believe that drug dispensing, as a basic and integrated service to health care networks, has great potential to promote the rational use of medicines and to screen patients who need additional, more complex, CPS.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to support from the community pharmacy chain were highlighted as facilitators of the implementation process. According to the literature, the support of the institution, the manager, and the supply of training, in uence the provision of CPS in different settings [15,26,27,36]. Regarding autonomy, studies have shown that this factor is in uenced by the market economy, often limiting the capacity for professionals, who are employed, to apply their own judgement when making decisions [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations